Search for a heavy charged boson in events with a charged lepton and missing transverse momentum from pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Hanke, Paul; Helary, Louis; Jongmanns, Jan; et al. (Physical review, 2019)
A search for a heavy charged-boson resonance decaying into a charged lepton (electron or muon) and a neutrino is reported. A data sample of 139 fb−1 of proton-proton collisions at √s=13 TeV collected with the ATLAS detector at the LHC during 2015-2018 is used in the search. The observed transverse mass distribution computed from the lepton and missing transverse momenta is consistent with the distribution expected from the Standard Model, and upper limits on the cross section for pp→W′→ℓν are extracted (ℓ=e or μ). These vary between 1.3 pb and 0.05 fb depending on the resonance mass in the range between 0.15 and 7.0 TeV at 95% confidence level for the electron and muon channels combined. Gauge bosons with a mass below 6.0 and 5.1 TeV are excluded in the electron and muon channels, respectively, in a model with a resonance that has couplings to fermions identical to those of the Standard Model W boson. Cross-section limits are also provided for resonances with several fixed Γ/m values in the range between 1% and 15%. Model-independent limits are derived in single-bin signal regions defined by a varying minimum transverse mass threshold. The resulting visible cross-section upper limits range between 4.6 (15) pb and 22 (22) ab as the threshold increases from 130 (110) GeV to 5.1 (5.1) TeV in the electron (muon) channel.
Gesehen am 30.10.2019
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, C. Antel, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, P. Hanke, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, J. Wang, S.M. Weber, M. Wessels, X. Yue [und 2921 weitere Personen]